Can a less boring ECB remain accountable? - Jean Pisani-Ferry; Jakob von Weizsäcker (Bruegel, 2009)
Through Bruegel's role on the Monetary Experts Panel for the European Parliament's Committee on Economic and Monetary Affairs, Bruegel scholars contributed to the Committee's Monetary Dialogue with the European Central Bank meeting on 28 September. In this briefing paper for the Panel, Director Jean Pisani-Ferry and Resident Fellow Jakob von Weizsäcker point out that, in the wake of the financial crisis, the ECB will take on much more responsibility for macro-prudential supervision of the financial system. With this added responsibility, however, comes serious questions about the mechanisms in place to ensure the ECB's accountability. Previously focused almost solely on price stability, the ECB will now likely be asked to increase its discretionary decision-making, especially in dealing with financial regulation. The accompanying accountability questions, the authors say, need to be addressed proactively.
Keywords: 330; Zentralbank; Geldpolitik; Finanzmarkt; Regulierung; Kapitalmarktrecht; Finanzmarktkrise; EU-Staaten